2018
DOI: 10.4236/ojvm.2018.84007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Pattern among the Mastitis Causing Microorganisms

Abstract: Mastitis is one of the most commonly occurring diseases of dairy animals. It is the most important cause of economic losses to the dairy industry in India and throughout the world. In the present study prevalence of microorganisms isolated from mastitic milk and their antibiotic resistance was studied. A total of sixty nine milk samples from mastitic animals (clinical and subclinical) were tested using sodium lauryl sulphate test and those positive were selected and transported to the laboratory for isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
2
10
1
1
Order By: Relevance
“…Even though the causes for emergence of antibiotic resistance are multifarious, there is wealth of evidence to suggest that milk consumption from cows that have been treated with antibiotics and are still within the withdrawal time period contributes significantly to the development of antimicrobial resistance in human beings (Sharma et al, 2018). Mastitis is one of the most commonly diagnosed infectious diseases in dairy cows and causes significant economic loss to the farmers (Singh et al, 2018;Chandrasekharan et al, 2014;Saini et al, 2012). Studies indicate that farmers across different parts of the country have incurred severe financial losses owing to outbreak of mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the causes for emergence of antibiotic resistance are multifarious, there is wealth of evidence to suggest that milk consumption from cows that have been treated with antibiotics and are still within the withdrawal time period contributes significantly to the development of antimicrobial resistance in human beings (Sharma et al, 2018). Mastitis is one of the most commonly diagnosed infectious diseases in dairy cows and causes significant economic loss to the farmers (Singh et al, 2018;Chandrasekharan et al, 2014;Saini et al, 2012). Studies indicate that farmers across different parts of the country have incurred severe financial losses owing to outbreak of mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…The present result also agrees with Idriss et al (2014) who found most of the isolated pathogens were sensitive to enrofloxacin. Furthermore, Singh et al (2018) reported that antibiogram for Streptococcus agalactiae revealed the highest sensitivity to ofloxacin, ciprofloxacin, gentamicin and resistance to amoxicillin and doxycycline; Staphylococcus aureus isolates were showed the highest sensitivity to ciprofloxacin, doxycycline, azithromycin and sparfloxacin and resistance to amoxycillin and gentamicin. Similarly, E. coli revealed the highest sensitivity to azithromycin and chloramphenicol and resistance to amoxicillin and teicoplanin.…”
Section: Table (3): Frequency Distribution Of Isolates From Subclinical Mastitismentioning
confidence: 99%
“…Antibiogram assessment of isolated bacteria is necessary tool for treatment and tracing the emergence of muti-drug resistance strain of such isolated bacteria. Many authors evaluated the sensitivity of isolated bacteria from subclinical mastitis against different antibiotics (Denamiel et al, 2005;Idriss et al, 2014 andSingh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a misuse of antibiotics in treating mastitits as well as the grwoth factor in sheep nutrition. The mechansim of antibiotic resistance is directly in charge of many cases of diseases treated with penicillin, tetracycline, erythromycin and others (5,7). Usually, in Nineveh region the commmon traditional treatment of sheep and goat mastitis is performed using antbiotics without sensevity test.…”
Section: Introductionmentioning
confidence: 99%